2012
DOI: 10.1002/ceat.201100276
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Kinetic Studies on a Homogeneous System for Diethyl Carbonate Synthesis by Transesterification

Abstract: A synthesis of diethyl carbonate through transesterification of propylene carbonate and ethanol, coproducing useful propylene glycol, was carried out in the presence of sodium ethoxide as catalyst. The effects of reaction parameters such as catalyst concentration, mole ratio of ethanol to propylene carbonate and reaction temperature on the transesterfication reaction were investigated. The results showed that the reaction is reversible with a propylene carbonate equilibrium conversion of about 64 % at an ethan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…Among them, sodium alkoxide was considered as the most promising catalyst for industrial application because of its low price and excellent performance. [267][268][269][270] However, considering corrosivity of sodium alkoxide, nonionic strong nitrogen bases were investigated by Williams et al 271 As shown in Table 15, entries 16-23, these strong nitrogen bases performed approximately as well as alkoxides, such as CH 3 ONa, CH 3 OLi. In consideration of the recycling of catalysts, Jagtap et al applied poly(4-vinylpyridine) as a novel, homogeneous base catalyst and it could be separated from reaction system by distillation or phase separation and showed little loss of activity after three recycles.…”
Section: Homogeneous Catalystsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among them, sodium alkoxide was considered as the most promising catalyst for industrial application because of its low price and excellent performance. [267][268][269][270] However, considering corrosivity of sodium alkoxide, nonionic strong nitrogen bases were investigated by Williams et al 271 As shown in Table 15, entries 16-23, these strong nitrogen bases performed approximately as well as alkoxides, such as CH 3 ONa, CH 3 OLi. In consideration of the recycling of catalysts, Jagtap et al applied poly(4-vinylpyridine) as a novel, homogeneous base catalyst and it could be separated from reaction system by distillation or phase separation and showed little loss of activity after three recycles.…”
Section: Homogeneous Catalystsmentioning
confidence: 99%
“…351 The reactant conversions of transesterification of cyclical carbonates and alcohols are also strongly limited by their unfavorable chemical equilibrium. 268,352 Furthermore, the formation of binary azeotropes between MeOH and DMC, EC and EG, makes the purification of DMC not only challenging but also energy and cost intensive. 353 Homogeneous processes, using a cheap alkali as catalyst, particularly CH 3 ONa, have great potential for commercialization.…”
Section: Reactive Distillation (Rd)mentioning
confidence: 99%
“…The main synthetic methods of DEC include urea alcoholysis, , transesterification of carbonate, direct synthesis route from ethanol and carbon dioxide (CO 2 ), and ethanol oxidative carbonylation . Many authors have reviewed these synthetic methods exhaustively. Notably, urea alcoholysis has a lower conversion rate because of evaporation of ethanol in the removal of ammonia during the reaction, transesterification of ethanol has a smaller equilibrium constant, carbonylation of ethanol using CO 2 is thermodynamically limited, and oxidative carbonylation of ethanol is a promising and quite favorable method because of its high atomic utilization rate.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, if released to the environment, DEC is biodegradable and will break down to CO 2 and ethanol. 5 DEC can be manufactured by a number of routes, 6 such as phosgenation of ethanol, 7 oxidative carbonylation of ethanol, 4 carbonylation of ethyl nitrile, 8 alcoholysis of urea, 9 and a two-step synthesis path 10 using CO 2 as feedstock to react either with propylene oxide or with ethylene oxide to form propylene carbonate (PC) or ethylene carbonate (EC), which is subsequently followed by transesterification with ethanol (EtOH) to produce DEC and either propylene glycol (PG) or ethylene glycol (EG).…”
Section: ■ Introductionmentioning
confidence: 99%